PENGARUH STORE ATMOSPHERE DAN BRAND EXPERIENCE TERHADAP MINAT BELI - Nilam Andini; Taufik Bustami (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to determine the effect of store atmosphere and brand experience on purchase intention for Mie Gacoan in Bengkulu City. This research is a quantitative descriptive study. The population was Mie Gacoan consumers in Bengkulu City, with a total sampling technique used. The data collection technique used was a questionnaire. Data analysis techniques included descriptive analysis, inferential analysis using SPSS, multiple linear regression analysis, and coefficient of determination (R2) analysis. The results of this study indicate that store atmosphere has a positive effect on purchase intention for Mie Gacoan in Bengkulu City. This means that the better the store atmosphere, the higher the consumer's purchase intention. Brand experience has a positive effect on purchase intention for Mie Gacoan in Bengkulu City. The better the brand experience perceived by consumers, the higher the purchase intention. Store atmosphere and brand experience simultaneously or together have a positive and significant effect on purchase intention for Mie Gacoan in Bengkulu City, indicating that both independent variables play a significant role in increasing consumer purchase intention. Keywords: Purchase Intention, Store Atmosphere, and Brand Experience.